An In Vivo Study Of A Locally-Manufactured Hydroxyapatite -Based Material As Bone Replacement Material. - Abdul Razak, N H; AL-Saiihi, K A; Samsudin, A R (2004)
Synthetic HA has excellent biocompatibility, but it has limited application due to its low toughness and flexural strength. In order to improve the mechanical properties (impact resistance, and tensile strength), metals and other elements were added to HA.